Eutectic Crystallization Activates Solid‐State Zinc‐Ion Conduction. (23rd November 2021) - Qiu, Huayu; Hu, Rongxiang; Du, Xiaofan; Chen, Zhou; Zhao, Jingwen; Lu, Guoli; Jiang, Meifang; Kong, Qingyu; Yan, Yiyuan; Du, Junzhe; Zhou, Xinhong; Cui, Guanglei
Abstract: Solid‐state zinc (Zn) batteries offer a new candidate for emerging applications sensitive to volume, safety and cost. However, current solid polymeric or ceramic electrolyte structures remain poorly conductive for the divalent Zn 2+, especially at room temperature. Constructing a heterogeneous interface which allows Zn 2+ percolation is a viable option, but this is rarely involved in multivalent systems. Herein, we construct a solid Zn 2+ ‐ion conductor by inducing crystallization of tailored eutectic liquids formed by organic Zn salts and bipolar ligands. High‐entropy eutectic‐networks weaken the ion‐association and form interfacial Zn 2+ ‐percolated channels on the nucleator surfaces, resulting in a solid crystal with exceptional selectivity for Zn 2+ transport ( t Zn 2 + =0.64) and appreciable Zn 2+ conductivity ( σ Zn 2 + =3.78×10 −5 S cm −1 at 30 °C, over 2 orders of magnitude higher than conventional polymers), and finally enabling practical ambient‐temperature Zn/V2 O5 metal solid cells. This design principle leveraged by the eutectic solidification affords new insights on the multivalent solid electrochemistry suffering from slow ion migration. Abstract : Here, we discovered a novel crystallized Zn 2+ conductor based on inducing crystallization of high‐entropy, charge‐separated eutectic liquids. To the best of our knowledge, it is the first introduction of the concept of a crystallized eutectic material to achieve dramatically enhanced multivalent‐ion transport properties. This facile strategy may also open up opportunities for designing a wide variety of new solid ionic conductors.